ANALISIS METODE PELAKSANAAN KINERJA PADA PEKERJAAN PRESERVASI JALAN BATAS KOTA PANGKALAN BUN-PANGKALAN LADA (Analysis Of Performance Implementation Methods In Pangkalan Bun-Pangkalan Lada City Limit Road Preservation Work) - Aria Hansen; M.Rafie Hamdi (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
The Directorate General of Highways through the Directorate of Road Preservation has implemented a new policy, namely road preservation using the long segment method for Indonesia's national roads. The long segment method aims to ensure that road pavements, shoulders, drainage systems, road auxiliary buildings and road equipment are at all times in a stable service condition based on the performance required in the contract documents. This research will discuss the suitability between expectations and the performance of Long Segment road preservation in the field using the Importance Performance Analysis (IPA) method. From the analysis of the IPA method by calculating the suitability between the level of performance received and the level of expectation for road performance, it will be known the satisfaction level of organizers and road users with the performance of Long Segment road preservation. The sample in this study were 10 expert respondents, from the Indonesian Bridge Road Development Association Professional Organization (HPJI), Academics, Commitment Making Officers (PPK), Consultants and Contractors. Keywords: Road, Terms of Reference, Long Segment